PENGARUH UTANG DAN PINJAMAN YANG DIBERIKAN (PYD) TERHADAP LABA BERSIH PADA PT PEGADAIAN DI KABUPATEN BONE - Muharrati, Ika; Idrus, Muhammad; Nurkurnia, Nurkurnia (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2024)
Research Objectives To determine the magnitude of the influence of debt on net profit at PT Pegadaian Bone Regency in 2023, To determine the magnitude of the influence of loans granted (PYD) on net profit at PT Pegadaian Bone Regency in 2023, To determine the magnitude of the influence of debt and loans granted (PYD) on net profit at PT Pegadaian Bone Regency in 2023. This research uses explanatory research which is explanatory in nature and aims to test a theory or hypothesis in order to strengthen or even reject existing theories or research hypotheses, as well as test the relationship or the relationship between variables, two or more variables. Research results 1) Debt does not have a significant influence on net profit at PT Pegadaian Bone. 2) Loans provided (PYD) have a significant influence on net profit at PT Pegadaian Bone. 3) Debt and loans granted (PYD) simultaneously have a significant influence on net profit at PT Pegadaian Bone.